El cónsul Thompson, los Bostonians y la formación de la galaxia Chichén, 1893-1904 - Palacios, Guillermo (El Colegio de México, A.C., 2015)
This article continues the narrative of the experiences of the businessmen-academics and collectors connected to Harvard University –the so-called Bostonians– in the archaeological sites of Yucatán, which were explored towards the end of the 1880s by Edward H. Thompson under their patronage, including his appointment as the U.S. consul in Mérida – as a form of protection – on their recommendation. This article reconstructs the loss of control of the strategic consulate by the Bostonians between 1893 and 1897. This narrative covers the occupation and the beginning of the looting of Chichen Itza, as well as the pseudo-scientific narrative the excavation provokes. It also analyzes the networks of alliances and rivalries resulting from the arrival of other U.S. archaeologists and archaeological institutions. It concludes with the paths Thompson pursued to undertake the adventure of his lifetime: the dredging of Chichen Itza’s Sacred Cenote.